Cimarron House Bed & Breakfast (Cimarron, New Mexico Cimarron Legend, 1992)
Advertisement for Cimarron House in Cimarron, New Mexico.
Master List item # 20
File location is in the Raton File Cabinet
Keywords: Davis, Stan; Davis, Ella; Cimarron House; Bed & Breakfast; Indoor pool; King size bed; Cimarron, New Mexico